Leveraging Content from Open Corpus Sources for Technology Enhanced Learning - LAWLESS, SEAMUS (Trinity College Dublin, 2009)
As educators attempt to incorporate the use of educational technologies in course curricula, the lack of appropriate and accessible digital content resources acts as a barrier to adoption. Quality educational digital resources can prove expensive to develop and have traditionally been restricted to use in the environment in which they were authored. As a result, educators who wish to adopt these approaches are compelled to produce large quantities of high quality educational content. This can lead to excessive workloads being placed upon the educator, whose efforts are better exerted on the pedagogical aspects of eLearning design. The accessibility, portability, repurposing and reuse of digital resources thus became, and remain, major challenges. The key motivation of this research is to enable the utilisation of the vast amounts of accumulated knowledge and educational content accessible via the World Wide Web in Technology Enhanced Learning (TEL). This thesis proposes an innovative approach to the targeted sourcing of open corpus content from the WWW and the resource-level reuse of such content in pedagogically beneficial TEL offerings. The thesis describes the requirements, both educational and technical, for a tool-chain that enables the discovery, classification, harvesting and delivery of content from the WWW, and a novel TEL application which demonstrates the resource-level reuse of open corpus content in the execution of a pedagogically meaningful educational offering. Presented in this work are the theoretical foundations, design and implementation of two applications: the Open Corpus Content Service (OCCS); and the User-driven Content Retrieval, Exploration and Assembly Toolkit for eLearning (U-CREATe). To evaluate and validate this research, a detailed analysis of the different aspects of the research is presented, outlining and addressing the discovery, classification and harvesting of open corpus content from the WWW and open corpus content utilisation in TEL. This analysis provides confidence in the ability of the OCCS to generate collections of highly relevant open corpus content in defined subject areas. The analysis also provides confidence that the resource-level reuse of such content in educational offerings is possible, and that these educational offerings can be pedagogically beneficial to the learner. A novel approach to the sourcing of open corpus educational content for integration and reuse in TEL is the primary contribution to the State of the Art made by this thesis and the research described therein. This approach differs significantly from those used by current TEL systems in the creation of learning offerings and provides a service which is considerably different to that offered by general purpose web search engines.
PUBLISHED
Keywords: Computer science